2017
DOI: 10.21273/hortsci12477-17
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Relative Growth Rate of Lettuce and Spinach in Hydroponics in a Greenhouse

Abstract: Relative growth rate (RGR), the relative increase in weight per day, can analyze the effect of environment and nutrition on growth. I examined which of the parameters responding to plant growth scaled according to RGR for lettuce and spinach grown in heated greenhouses in hydroponics with control of the nutrient solution. The experiments for lettuce in 2006–08 included all times of year, high vs. low temperature, and effect of withdrawal of nitrogen. There were four parameters that were significant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Finally, as reported in Table 2, the relative growth rate (RGR) calculated for treated seedlings resulted to be significantly higher than that estimated in control lettuce. Gent [26] showed that in lettuce the RGR, representing the relative increase in weight per day, slowly changes when plants grow in a constant environment, whereas environmental and nutritional alterations have effects on their growth. Therefore, being fixed in the experimental conditions, as it is in the present trial, the increase of RGR in treated lettuce was certainly linked to the biostimulant effect of CV extract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as reported in Table 2, the relative growth rate (RGR) calculated for treated seedlings resulted to be significantly higher than that estimated in control lettuce. Gent [26] showed that in lettuce the RGR, representing the relative increase in weight per day, slowly changes when plants grow in a constant environment, whereas environmental and nutritional alterations have effects on their growth. Therefore, being fixed in the experimental conditions, as it is in the present trial, the increase of RGR in treated lettuce was certainly linked to the biostimulant effect of CV extract.…”
Section: Resultsmentioning
confidence: 99%
“…Relative growth rate (RGR) was determined, as reported in Gent [26], from the shoot weights harvested just before the treatment and at the end of the experimental period (21 days after the first treatment) using the following equation:…”
Section: Morpho-biometric and Physiologic Parameters In Lettuce Seedlmentioning
confidence: 99%
“…The differences of atmospheric [CO 2 ] and temperature between AT and ET were recorded as 5-8 ppm and 5°C during 9 am to 5.59pm hours and 9-11ppm and 1°C during 6pm to next day 8.59 am. Relative growth rate is the mathematical interpretation of relative increase of plant dry weight per day and RGR reveals the relative impact of environment on plant growth (Gent, 2017 andSonsteby, et al, 2016). Plant RGR analysis data in vegetative phase, had no significant difference between varieties but had a significance difference between two temperature regimes.…”
Section: Resultsmentioning
confidence: 99%
“…They found that planting dates in September or April (warmer cropping season) resulted in a shorter growth cycle than those in December or January (cooler cropping season). Environmental factors such as temperature and light are well known to positively influence growth traits (De Pinheiro Henriques and Marcelis, 2000;Gent, 2017;Hatfield and Prueger, 2015). In that sense, higher daytime temperatures during the spring season resulted in more heat unit accumulation, likely leading to greater growth rates due to enhanced photosynthetic functions.…”
Section: Discussionmentioning
confidence: 99%